Transformational Female Leadership as a Strategic Factor in Enhancing Educational Quality in Pesantren - Intan Istiqomah; Ahmad Azkal Azkiya (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
Leadership in Islamic boarding schools (pesantren) has historically been dominated by men, yet the rise of female leadership introduces new perspectives on educational management and quality assurance. This study critically examines the forms, characteristics, and strategies of female leadership in a traditional Islamic boarding school in East Java and evaluates its impact on educational quality. Employing a qualitative case study, data were collected through observation, interviews with female administrators, teachers, musyrifah, abdi ndalem, and dormitory supervisors, as well as documentation, and analyzed using Miles and Huberman’s interactive model. Findings reveal that female leadership is marked by transformational, participatory, meticulous, and guidance-oriented practices, with strategies such as strict supervision, collaborative communication, emotional support, and student-centered innovations. These approaches strengthen discipline, enhance learning quality, foster a harmonious dormitory environment, and reinforce religious and character education. The study concludes that female leadership is a strategic driver of educational quality in Islamic boarding schools and provides a replicable model for policymakers, educators, and researchers seeking to advance gender-inclusive leadership in Islamic education.